EVALUATION OF SEED GERMINATION ABILITY AND EX SITU AND IN VITRO CULTIVATION OF A PROMISING REPRESENTATIVE OF THE GENUS ALLIUM L. – ALLIUM PSKEMENSE B. FEDTSCH. (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Analysis of the swelling process revealed some differences in the kinetics in A.pskemense B. Fedtsch. from 2 other representatives of the genus Allium L. – A. aflatunense B.Fedtsch.and A. altissimum Regel. A. pskemense B. Fedtsch plants were introduced into in vitro culture onMurashige and Skoog + 0.5 6-benzylaminopurine medium. Callus culture obtained from the rootson Murashige and Skoog medium with the addition of 1.0 mg/l of 2,4-dichlorophenoxyacetic acid,0.2 mg/l of 6-benzylaminopurine and 30 g/l of sucrose. The period of callus formation is about 3months.
Keywords: Allium L., A. pskemense B.Fedtsch., ex situ, in vitro.